Emotional resiliency and life satisfaction among teachers of Chinese as a foreign language: mediating chain model with grit and employability and gender moderation - Yicun Jia (Frontiers in Psychology)
ObjectiveTo investigate the relationships between emotional resilience, grit, employability, and life satisfaction among Chinese as a Foreign Language (CFL) teachers in China, with a focus on gender differences.MethodsA sample of 1,003 CFL teachers participated in a survey assessing emotional resilience, grit, employability, and life satisfaction. Data were analyzed using descriptive statistics, correlation analyses, and mediation and moderation models with the PROCESS macro.ResultsEmotional resilience did not have a significant direct effect on life satisfaction but showed substantial indirect effects through grit and employability. Emotional resilience positively influenced grit, which in turn enhanced employability and increased life satisfaction. Gender differences were observed grit was a more critical mediator for males, while employability was a stronger mediator for females.ConclusionThe study highlights the importance of grit and employability in enhancing life satisfaction among CFL teachers. Gender-specific interventions to bolster these mediating factors are recommended to support the wellbeing and professional success of CFL teachers.ImplicationsEducational institutions should develop professional development programs and support systems that foster emotional resilience, grit, and employability, with attention to gender-specific needs, to improve job satisfaction and effectiveness among CFL teachers.